Workplace violence among nurses of a teaching hospital - Paudel, Sadhana (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Workplace violence is a significant issue in the health sector with high prevalence. Workplace violence among nurses is an alarming and fundamental human rights issue with its negative impacts on nurses as well as organizational achievement. This study aimed to explore workplace violence among nurses. Method: Cross-sectional study design with a total enumerative sampling technique was used to find out the prevalence of workplace violence among 402 nurses of a teaching hospital in Lalitpur, Nepal. Data was collected by using “Workplace Violence in the Health Sector country case studies research Instruments” from September 2019 to November 2019. Collected data were analyzed based on objectives using Statistical Package for Social Science version 16. Descriptive statistics were used to find out the prevalence, types of violence, perpetrators, and socio-demographic information. Result: The prevalence of workplace violence was 227( among which verbal abuse was 215(94.5%), physical violence 40(17.6%), and sexual harassment 9(4%). Among the perpetrators, 107(40.53%) of workplace violence was done by patients’ relatives, 77(29.16%) by patients, 64(24.24%) by staff, and 16(6.06%) by management. Conclusion: The prevalence of workplace violence is high. Verbal abuse is the dominant type of violence, followed by physical violence and sexual harassment. The main perpetrators of workplace violence were patients’ relatives. Management was also found to be the perpetrator in a small fraction of violence.